Optimasi Micro-Learning dalam Pendidikan Islam: : Analisis Kegiatan Halaqah di Pondok Pesantren Darullughah Wadda’wah - Sahrandi, Akhmad (Jurnal Tinta, 2025)
This research aims to analyze the optimization of micro-learning strategies within the Hadramiyyah Halaqah tradition at the Darullughah Wadda’wah Islamic Boarding School (Dalwa). Amidst a dense formal curriculum and the declining concentration spans characteristic of Generation Z, Dalwa consistently maintains short-duration learning sessions (20–25 minutes) conducted entirely in introductory Arabic. Employing a qualitative case study approach, data were collected through participant observation, in-depth interviews, and documentation. The analysis was conducted through the theoretical lenses of Cognitive Load Theory and the concept of spaced repetition. The findings reveal that the brief yet consistent session duration successfully mitigates cognitive overload and enhances students' long-term retention of classical religious texts (kitab kuning). The absolute use of Arabic functions as a focus catalyst, fostering an immersive learning ecosystem. Furthermore, the point-centric teaching methodology and the intentional limitation of dialectical interaction prove effective in efficiently transferring complex subject matter. This study concludes that the halaqah model at Dalwa represents a form of traditional pedagogical innovation that holds significant relevance for the educational efficiency demands of the 21st century. Theoretically, this research contributes to the development of Islamic boarding school curriculum management frameworks that balance traditional resilience with the exigencies of modernity.